Impact of Economic Policy Uncertainty on Exchange Market Pressure - Olanipekun, Ifedolapo Olabisi; Olasehinde-Williams, Godwin; Gungor, Hasan (Sage Publications Inc, 2019)
Capturing changes in foreign reserves and exchange rates through the exchange market pressure, this article investigates whether economic policy uncertainty plays any role in exchange market pressure movements while controlling for the effects of domestic and external factors. A panel of 20 countries was examined from 2003Q1 to 2017Q4 using panel techniques that are consistent in the presence of heterogeneity and cross-sectional dependence. The study finds that a long-run relationship exists between exchange market pressure and economic policy uncertainty. Our estimation results reveal that a rise in economic policy uncertainty, consumer price index, trade openness, and financial openness increases the severity of the exchange market pressure in the long run. However, gross domestic product (GDP) growth, domestic credit, and foreign direct investment inflows can cushion the effect of the pressure. Therefore, irrespective of whether a country operates fixed, flexible, or intermediate exchange rate regime, its foreign exchange market is still significantly affected by economic policy uncertainty.
Keywords: exchange market pressure; economic policy uncertainty; long-run relationships